ANALISIS PERILAKU KESEHATAN IBU YANG BERPENGARUH DENGAN KEJADIAN STUNTING DI WILAYAH KERJA PUSKESMAS PEMULUTAN KABUPATEN OGAN ILIR TAHUN 2023 - Redi Kaswara; Erma Gustina; Gema Asiani; Dianita Eka Wati (Avicenna: Jurnal Ilmiah, 2023)
Background: Stunting is a chronic malnutrition problem caused by a lack of nutritional intake for a long time, this causes future problems, namely experiencing difficulties in achieving optimal physical and cognitive development. Children with stunting have a lower Intelligence Quotient (IQ) than the average IQ of normal children. This study aims to determine the Analysis of Maternal Health Behavior Affected by Stunting Incidents in the Pemulutan Health Center Work Area, Ogan Ilir Regency in 2023. Methods: The design of this study used Cross Sectional, where the population in this study was 206 respondents, with a sample of 67 respondents who visited. The sampling method in this study was purposive sampling. This research was carried out on June 15-20 in 2023. Data collection and retrieval using questionnaires and observation. Results: The results of the statistical test analysis using the Chi-Square statistical test and logistic regression where the results showed that there was a significant relationship (p value <0.05) for the variables age (p value 0.032), mother's education (p value 0.016), mother's occupation (p value 0.024) mother's knowledge (p value 0.026), exclusive breastfeeding (p value 0.027) ANC visits (p value 0.041), smoking behavior (p value 0.001) and defecation behavior (p value 0.011) while the unrelated variables are type sex (p value 0.562). From the results of the multivariate statistical test, it was found that the dominant factor in the incidence of stunting was ANC visits (p= 0.007; OR= 108.598). Conclusion: It is hoped that health workers can improve nutritional status checks, immunization checks on pregnant women, nursing mothers so that the risk of stunting can be prevented as early as possible so that no more toddlers will be stunted.   Keywords: Toddlers, Behavior, Stunting